2013
DOI: 10.1161/jaha.113.000201
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐Like 2 Promotes Atherogenesis in Mice

Abstract: BackgroundAngiopoietin like‐2 (angptl2), a proinflammatory protein, is overexpressed in endothelial cells (ECs) from patients with coronary artery disease (CAD). Whether angptl2 contributes to atherogenesis is unknown. We tested the hypothesis that angptl2 promotes inflammation and leukocyte adhesion onto ECs, thereby accelerating atherogenesis in preatherosclerotic dyslipidemic mice.Methods and ResultsIn ECs freshly isolated from the aorta, basal expression of TNF‐α and IL‐6 mRNA was higher in 3‐month‐old sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 39 publications
8
101
1
Order By: Relevance
“…In two recent reports, it was shown that angptl2 promoted endothelial dysfunction in a pro-atherogenic environment, decreased relaxation and expression of phosphoeNOS (20), increased leukocytes adhesion, and ultimately accelerated atherogenesis (12). Our demonstration that knockdown of angptl2 favors NO-dependent dilation in cerebral arteries therefore suggests that angptl2 plays a role in reducing endothelial cell stress resistance.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…In two recent reports, it was shown that angptl2 promoted endothelial dysfunction in a pro-atherogenic environment, decreased relaxation and expression of phosphoeNOS (20), increased leukocytes adhesion, and ultimately accelerated atherogenesis (12). Our demonstration that knockdown of angptl2 favors NO-dependent dilation in cerebral arteries therefore suggests that angptl2 plays a role in reducing endothelial cell stress resistance.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, knockdown of angptl2 may be associated with beneficial effects of a Nox, likely Nox4, an isoform that predominantly produces dilatory H 2 O 2 . Taken together, preventing the demonstrated rise of angptl2 through age (20) and atherosclerosis (12,20) may emerge as a new therapeutic concept to increase endothelial cell stress resistance and delay atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations